Detection of antidrug antibodies against human therapeutic antibodies lacking Fc-effector functions by usage of soluble Fcγ receptor I. (October 2016) - Wessels, Uwe; Poehler, Alexander; Moheysen-Zadeh, Miriam; Zadak, Markus; Staack, Roland F; Umana, Pablo; Heinrich, Julia; Stubenrauch, Kay
Aim: Bridging immunoassays for the detection of antidrug antibodies (ADAs) are limited to detection of bivalent molecules and are prone to interference by drug and soluble targets. Hence, alternative approaches for ADA detection are desired.Materials & methods: A novel ADA assay with secondary Fc detection using human soluble Fcγ receptor I (hsFcγRI) was established and compared with standard bridging assay.Results: Both assays showed consistent results in human and cynomolgus monkey samples. In contrast to the bridging assay, the hsFcγRI-based assay was insensitive to the presence of oligomeric targets and appeared to have better drug tolerance.Conclusion: The hsFcγRI-based ADA assay can serve as alternative screening assay or as orthogonal confirmation method for preclinical and clinical immunogenicity testing of IgG therapeutics lacking Fc effector functions.